Dampak Kepemimpinan, Motivasi Kerja Dan Kompetensi Terhadap Kinerja Pegawai Serta Implikasinya Pada Kualitas Perencanaan Pembangunan - Rahmat Rukmana (Kontigensi : Jurnal Ilmiah Manajemen, 2016)
The purpose of this study was to analyzethe role of state leadership, motivation, competence, staff performance and quality development planning and to see the high contribution the influence the role of leadership, motivation and competence staff performance and their impact on the quality of development planning. The studies are descriptive methods and verificative. Descriptive method using the assessment scores of the study variables. Verificative using path analysis method (Path Analysis) which aims to determine the causal relationships between variables of the study, and hypothesis testing. The unit analysis on this research is the employees of Bappeda WKPP III West Java Province, with number of sample196 peoples and using clustered stratified randomsampling technique. The results prove that descriptively, the role of leadership, motivation and work performance employees are on the scale of good, but his achievements have not been optimal. Verificative research results prove that, there is a significant contribution to the role of leadership, motivation and competence staff performance and quality development planning, either simultaneously or partial.